Oxygen in patients with fibrotic interstitial lung disease: an international Delphi survey. Issue 2 (8th August 2019) - Lim, Rachel K.; Humphreys, Christopher; Morisset, Julie; Holland, Anne E.; Johannson, Kerri A.
Rationale: Patients with fibrotic interstitial lung disease (ILD) frequently develop resting or exertional hypoxaemia. There is heterogeneity in clinical practice and a paucity of evidence guiding supplemental oxygen use in this patient population. The objectives of this study were to build international expert-based consensus on the indications and goals of supplemental oxygen from the perspective of healthcare providers, and identify potential barriers to its access. Methods: Semistructured interviews and a comprehensive literature search informed items for the Delphi survey, with items not meeting consensus included in round 2. Round 3 contained survey questions regarding regional funding coverage for oxygen therapy. A priori definitions of consensus were median scores of 4 (agree) to 5 (strongly agree) for "agreement", 1 (strongly disagree) to 2 (disagree) for "disagreement" or 3 (unsure) with an interquartile range of 0–1. Results: 42 out of 45 (93%) experts completed all three survey rounds, representing 17 countries. 20 out of 36 items met consensus for agreement or disagreement, 10 items met consensus for unsure and four items did not meet consensus. Experts agreed that oxygen should be recommended for patients with severe resting hypoxaemia and in cases of exertional desaturation to <85–89%, particularly with attributable symptoms or exercise limitation. There are regional differences in funding coverage for oxygen, based on desaturation thresholds, clinical symptoms and testing requirements. Conclusions: Experts achieved consensus on 20 items guiding supplemental oxygen use in fibrotic ILD. These findings may inform research, clinical recommendations and funding policy. Supplemental oxygen should be recommended for patients with fibrotic interstitial lung disease in cases of severe resting hypoxaemia, or exertional hypoxaemia particularly with attributable symptoms or exercise limitation http://bit.ly/2Hsq6sq